The judicial pursuit of the sexual victimization of children: how the criminal justice system processes cases - Tamarit Sumalla, Josep Maria (International review of victimology, 2017)
This article analyses the criminal justice system’s treatment of those sexual offences against children of which it is made aware. The findings reported in this article draw on a quantitative study based on data (n = 97) taken from judicial files from a province of Catalonia, Spain. The study examines prosecution, trial and conviction rates, analysing the possible variables involved to provide a better understanding of the reasons behind the successful prosecution of complaints made. The study points to a low rate of prosecution, similar to other studies carried out in English-speaking countries. This leads us to conclude that differences in legal systems do not give rise to significant differences in dealing with cases. There is no evidence that a legalistic system such as that of Spain acts as a restraining element against the influence of non-legal factors in the judicial decision-making process. However, similarities with other studies are not found with regards to some factors associated with it. The findings provide no confirmation of the hypothesis that the Spanish criminal justice system is particularly reluctant to prosecute cases of intrafamilial victimization.